Biologically active recombinant human erythropoietin expressed in hairy root cultures and regenerated plantlets of Nicotiana tabacum L. - Gurusamy, Poornima Devi; Schäfer, Holger; Wink, Michael (PLOS ONE, 2017)
Hairy root culture is a potential alternative to conventional mammalian cell culture to produce recombinant proteins due to its ease in protein recovery, low costs and absence of potentially human pathogenic contaminants. The current study focussed to develop a new platform of a hairy root culture system from Nicotiana tabacum for the production of recombinant human EPO (rhEPO), which is regularly produced in mammalian cells. The human EPO construct was amplified with C-terminal hexahistidine tag from a cDNA of Caco-2 cells. Two versions of rhEPO clones, with or without the N-terminal calreticulin (cal) fusion sequence, were produced by cloning the amplified construct into gateway binary vector pK7WG2D. Following Agrobacterium rhizogenes mediated transformation of tobacco explants; integration and expression of constructs in hairy roots were confirmed by several tests at DNA, RNA and protein levels. The amount of intracellular rhEPO from hairy root cultures with cal signal peptide was measured up to 66.75 ng g-1 of total soluble protein. The presence of the ER signal peptide (cal) was essential for the secretion of rhEPO into the spent medium; no protein was detected from hairy root cultures without ER signal peptide. The addition of polyvinylpyrrolidone enhanced the stabilization of secreted rhEPO leading to a 5.6 fold increase to a maximum concentration of 185.48 pg rhEPOHR g-1 FW hairy root cultures. The rhizo-secreted rhEPO was separated by HPLC and its biological activity was confirmed by testing distinct parameters for proliferation and survival in retinal pigment epithelial cells (ARPE). In addition, the rhEPO was detected to an amount 14.8 ng g-1 of total soluble leaf protein in transgenic T0 generation plantlets regenerated from hairy root cultures with cal signal peptide.